Pairing of two highly sexually dimorphic species within the genus Lophocampa Harris, 1841 (Lepidoptera: Erebidae: Arctiini) - Laguerre, Michel; Vincentcent, Benoit (Zootaxa, 2021)
Two Lophocampa species previously known only by females are paired with morphologically highly different male specimens. This pairing was initiated after the discovery of a mosaic gynandromorph specimen and then confirmed using the mitochondrial COI gene (the so-called DNA barcode). Following the discovery of a labeling error by Rothschild during the original description of two species, two recombinations are proposed. Pairs for each species are illustrated and the male specimens are described for the first time.